(untitled) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2015)
Sulalat us-Salatin is one of the most important literary sources about the origins of Malay civilization and the geneology of the Malay kings. The objective of this study was to analyse the sayings of Prophet Muhammad as quoted in this book. This study used a qualitative method whereby all of the sayings were critically analysed using content analysis, and the authenticity of the sayings was also evaluated. As a result, only two out of four quotations are considered to be authentic sayings of Prophet Muhammad. This study shows that Islam has strongly influenced Malay writing traditions even where historical literature is concerned. Keywords: Sulalat us-Slatin hadith, Sejarah Melayu, Islam, malay Archipelago